Building Corporate Value Through Green Finance and Environmental Performance - Lubis, Tona Aurora; Yuliusman; Andang Fazri; Muhammad Haris Saputra (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the Impact of Green Finance and Environmental Performance on Firm Value through Financial Performance. This objective is described as: 1) Analyzing the influence of Green finance, environmental performance and financial performance on firm value in Consumer Non-Cyclicals Sector Companies for the 2020-2023 Period 2) Analyzing the influence of Green finance and environmental performance on financial performance in Consumer Non-Cyclicals Sector Companies for the 2020-2023 Period 3) Analyzing the influence of Green finance and environmental performance on firm value through financial performance as a mediating variable in Consumer Non-Cyclicals Sector Companies for the 2020-2023 Period. This study is a quantitative study using SEM PLS. The results show that environmental performance has a positive and significant effect on financial performance, and financial performance is proven to have a strong and significant effect on firm value, while environmental performance does not directly affect firm value without the mediation of financial performance; On the other hand, Green Finance does not have a significant influence on either financial performance or company value, and is not proven to mediate the relationship, so it can be concluded that financial performance is a key factor that mediates the influence of environmental performance on company value, while green finance has not shown a significant contribution in the context of Consumer Non-Cyclicals sector companies in Indonesia for the period 2020–2023.